Cybersecurity Defence Systems for Malaysia Digital Economy - Muhamad Khairulnizam ZAINI; Norhayati HUSSIN; Irni Eliana KHAIRUDDIN; Zainal Abidin MOHD JAIS (Communications of International Proceedings, 2020)
Cyber security risks and threats have increased in recent years, causing significant economic and social losses to public and private organisations as well as individuals. Discourses around these problems have driven government initiatives and academic research in Malaysia to focus on protecting critical national information infrastructure (CNII), the public and governments. In contrast, there has not been much attention given to the impact of cyber threats on business organisations, especially in the digital economy era. The recent data from Cyber Security Malaysia (CSM) stated that in the year 2019 alone, more than 10,700 cyber security attacks on corporations, business organisations and individuals nationwide for incidents such as ransomware, malicious attacks, data breaches were recorded, indicating that cyber-threats are together growing in digital ecosystems. There has not been much attention given to the impact of exposure of Malaysian businesses to high levels of cyber-attacks, especially those related to the digital economy era. The lack of attention to this research area indicates that cyber security management in this new age economy is an uncharted territory and requires further investigation. The objective of this paper is to discuss the comprehensive landscape of cyber security management in Malaysia’s business context. Particularly, the aims of this paper are to propose on how organizations can develop a comprehensive defence system, incorporating situational awareness systems, threat intelligence analysis, and effective security operation platforms and trust technology for digital economy.
Keywords: Cyber Security; Digital Economy; Security Analytics; Blockchain; Digital Business